Modelling cognitive outcomes in the UK Biobank: Education, noradrenaline and frontoparietal networks - Laura Bravo-Merodio; Jackie A. Olley-Williams; Dominic Russ; Georgios Gkoutos; Meadhbh B. Brosnan; Mark A. Bellgrove; Magdalena Chechlacz (PLoS ONE, 2026)
Education is often used as a surrogate measure of so called cognitive reserve (CR) benefiting cognitive functioning in later years. In line with Robertson’s theory we tested here a hypothesis that education acting on the noradrenergic system strengthen the right fronto-parietal networks to facilitate CR and maintain cognition throughout the lifetime. We used machine learning and mediation analysis to model interactions between neurobiological features (genetic variants in noradrenergic signalling, structural and functional fronto-parietal connectivity) and education (proxy of CR) on cognitive outcomes (measured here by general cognitive ability score calculated based on performance across a battery of cognitive tests) in the UK Biobank cohort. We show that: (1) interactions between education and neurobiological variables better explain cognitive outcomes than either factor alone; (2) among the neurobiological features selected using variable importance testing, measures of right fronto-parietal connectivity are the strongest mediators of the association between education and cognitive outcomes. Our findings offer novel insights into neurobiological basis of CR by pointing to between-networks connectivity, representing connections linking the default mode network with the right fronto-parietal network as the key facilitator of CR.